1988
DOI: 10.3354/meps042053
|View full text |Cite
|
Sign up to set email alerts
|

Carbon transport between a euhaline vegetated marsh in South Carolina and the adjacent tidal creek: contributions via tidal inundation, runoff and seepage

Abstract: Exchange of organic carbon (DOC and POC) between a euhaline vegetated marsh and an adjacent tidal creek (North Inlet, South Carolina) was studled on 40 tidal cycles between 15 Apr 1983 and 19 Jun 1984. A flume was utilized to evaluate the role of the vegetated marsh in processing carbon during tidal inundation and a drainage weir was used to measure export from the marsh via runoff and seepage during low tide exposure (including storm events). Mean flood water DOC concentrations varied seasonally from 3.1 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
19
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 15 publications
3
19
0
1
Order By: Relevance
“…As in the present study (Fig. 8), both Lee (1979) and Wolaver et al ( 1983) found a correlation between uptake by the marsh and nutrient concentrations in the flooding water. These past studies and present results suggest that the seasonal pattern of inorganic nitrogen import is more dependent on the concentration of nutrients in water flooding the marsh than on the seasonal demand of primary producers in the marsh.…”
supporting
confidence: 69%
See 3 more Smart Citations
“…As in the present study (Fig. 8), both Lee (1979) and Wolaver et al ( 1983) found a correlation between uptake by the marsh and nutrient concentrations in the flooding water. These past studies and present results suggest that the seasonal pattern of inorganic nitrogen import is more dependent on the concentration of nutrients in water flooding the marsh than on the seasonal demand of primary producers in the marsh.…”
supporting
confidence: 69%
“…The net result was a loss of nitrogen from the marsh to the creek dominated by dissolved organic nitrogen export during inundation and drainage (Table 2). Previous exchange studies on the marsh surface indicated similar results for inorganic nitrogen (Lee 1979;Wolaver et al 1983), but seasonal patterns of exchange did vary among sites. A Virginia mesohaline marsh (Wolaver et al 1983) had peak imports of inorganic nitrogen during early spring and fall, apparently related to elevated concentrations of inorganic nitrogen flooding the marsh because of increased agricultural activities.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…It has been found that these episodic events may result in a pulse of POM suspended in the marsh runoff (Chalmers et al 1985;Wolaver and Spurrier 1988). Roman and Daiber (1989) noticed the presence of plant fragments in the ebbtide water under these circumstances and attributed it to vigorous flushing and erosion of the marsh surface.…”
Section: Shifts In Seston Characteristics After Inundation Of a Europmentioning
confidence: 99%